Area postrema syndrome in patients with autoimmune glial fibrillary acidic protein astrocytopathy - Qingchen Li; Junfang Teng (Frontiers in Neurology)
ObjectiveArea postrema syndrome (APS) is a relatively rare symptom of autoimmune glial fibrillary acidic protein astrocytopathy (A-GFAP-A). This study aimed to report the APS in GFAP-immunoglobulin G (GFAP-IgG) positive patients.MethodsWe retrospectively analyzed the clinical data of APS in GFAP-IgG positive patients and reviewed relevant literature. Moreover, we compared these data with APS patients in aquaporin-4-IgG-positive neuromyelitis optica spectrum disorders (AQP4-IgG+ NMOSD).Results7 of 75 (9.3%) GFAP-IgG positive patients experienced APS, including 4 females and 3 males. The median age of onset was 42 years (range, 12–71 years). All patients presented with APS as their initial manifestation. Nausea and vomiting were observed in all 7 patients, while hiccups occurred in 5 patients. The median duration of APS episodes was 12 days (range, 6–40 days). None of the patients experienced isolated APS episodes during their illness. AQP4-IgG was positive in 2 patients. 5 patients had dorsal medulla oblongata lesions, while 3 patients showed an “inverted V” sign on axial images. In addition, 5 patients presented with longitudinally extensive linear or patchy lesions in cervical spinal cord extending to area postrema on sagittal images. All APS attacks completely disappeared after immunotherapy. Compared with the APS in AQP4 + NMOSD, APS in A-GFAP-A had a lower proportion of females (33.3% vs. 80%, p = 0.003), more hiccups (81% vs. 50%, p = 0.037), more leptomeningeal enhancement (61.9% vs. 5%, p = 0.000), higher CSF white blood cell count (median 120 vs. 10 cells/mm3, p = 0.000) and protein (median 0.949 vs. 0.407 g/L, p = 0.000). Furthermore, fewer patients with A-GFAP-A received long-term immunotherapy (19% vs. 65%, p = 0.003).ConclusionAPS often occurs as an initial manifestation of A-GFAP-A. MRI examination and antibody testing should be performed in suspected patients to avoid misdiagnosis.